2015
DOI: 10.1007/s10689-015-9862-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thyroid cancer among Caribbean Hispanic patients with familial adenomatous polyposis

Abstract: Background & Aims Familial adenomatous polyposis (FAP) is an inherited form of colorectal cancer (CRC) characterized by hundreds of adenomatous polyps in the colon and rectum. FAP is also associated with thyroid cancer (TC), but the lifetime risk is still unclear. This study reports the standardized incidence ratio of TC in Hispanic FAP patients. Methods TC incidence rates in patients with FAP were compared with the general population through direct database linkage from the Puerto Rico Central Cancer Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In FAP associated cases (about 60% of the total), thyroid carcinoma diagnosis precedes that of familial adenomatous polyposis in up to 40% of the cases [15,18,30,36,44,53,67]. The risk and incidence rate of cribriformmorular variant of thyroid carcinoma in Hispanic patients with familial adenomatous polyposis seems to be higher than in other reported groups [68].…”
Section: Epidemiologymentioning
confidence: 74%
“…In FAP associated cases (about 60% of the total), thyroid carcinoma diagnosis precedes that of familial adenomatous polyposis in up to 40% of the cases [15,18,30,36,44,53,67]. The risk and incidence rate of cribriformmorular variant of thyroid carcinoma in Hispanic patients with familial adenomatous polyposis seems to be higher than in other reported groups [68].…”
Section: Epidemiologymentioning
confidence: 74%
“…Lynch syndrome was associated with an increased risk of certain malignancies in the colorectum, uterus, ovary, stomach, small intestine, urine epithelial tissues, central neural system, pancreas, and breast, whereas familial adenomatous polyposis was associated with a high tendency to develop cancers derived from the thyroid and duodenum 20–24. The current study indicated that the risk of cancer was high for the small intestine, colorectum, uterus, renal pelvis, thyroid, and stomach in CRC survivors, especially in young patients, whereas it was low for cancers of the gallbladder, liver, and brain, as well as myeloma and lymphoma, especially in old patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lynch syndrome is caused by germline mutations and is associated with an increased risk of colorectum, stomach, small intestine, and pancreatic cancers, as well as other genitourinary cancers (24)(25)(26)(27). Similarly, hereditary non-polyposis CRC, which is attributed to mutations in the DNA mismatch repair genes, increases the risk of developing multiple primary CRCs and tumors at extracolonic sites, including the endometrium, ovary, small intestine, biliary tract, urinary tract, stomach, kidney, thyroid, and nervous system (16,28,29). In the present study, we established that specific risks of SPMs varied with the histological subtypes of CRC.…”
Section: Discussionmentioning
confidence: 99%